Effectiveness of non-pharmacological strategies in the management of type 2 diabetes in primary care: A protocol for a systematic review and network meta-analysis - Leite, Renata Giacomini Oliveira Ferreira [UNESP]; Banzato, Luísa Rocco [UNESP]; Galendi, Julia Simões Corrêa [UNESP]; Mendes, Adriana Lucia [UNESP]; Bolfi, Fernanda [UNESP]; Veroniki, Areti Angeliki; Thabane, Lehana; Nogueira, Vania dos Santos Nunes [UNESP] (BMJ, 2020)
Introduction Despite the increasing number of drugs and various guidelines on the management of type 2 diabetes mellitus (T2DM), several patients continue with the disease uncontrolled. There are several non-pharmacological treatments available for managing T2DM, but various of them have never been compared directly to determine the best strategies. Objective This study will evaluate the comparative effects of non-pharmacological strategies in the management of T2DM in primary care or community settings. Methods and analysis We will perform a systematic review and network meta-analysis (NMA), and will include randomised controlled trials if one of the following interventions were applied in adult patients with T2DM: nutritional therapy, physical activity, psychological interventions, social interventions, multidisciplinary lifestyle interventions, diabetes self-management education and support (DSMES), technology-enabled DSMES, interventions delivered only either by pharmacists or by nurses, self-blood glucose monitoring in non-insulin-treated T2DM, health coaching, benchmarking and usual care. The primary outcome will be glycaemic control (glycated haemoglobin (HbA1c) (%)), and the secondary outcomes will be weight loss, quality of life, patient satisfaction, frequency of cardiovascular events and deaths, number of patients in each group with HbA1c <7, adverse events and medication adherence. We have developed search strategies for Embase, Medline, Latin American and Caribbean Health Sciences Literature, Cochrane Central Register of Controlled Trials, Trip database, Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature Australasian Medical Index and Chinese Biomedical Literature Database. Four reviewers will assess the studies for their eligibility and their risk of bias in pairs and independently. An NMA will be performed using a Bayesian hierarchical model, and the treatment hierarchy will be obtained using the surface under the cumulative ranking curve. To determine our confidence in an overall treatment ranking from the NMA, we will follow the Grading of Recommendations Assessment, Development and Evaluation approach. Ethics and dissemination As no primary data collection will be undertaken, no formal ethical assessment is required. We plan to present the results of this systematic review in a peer-reviewed scientific journal, conferences and the popular press. PROSPERO registration number CRD42019127856.
Keywords: diabetes mellitus type 2; network meta-analysis; primary health care; systematic review